Privacy Is Precious: On the Attempt to Lift Anonymity on the Internet to Increase Revenue. Issue 2 (7th February 2017) - Regner, Tobias; Riener, Gerhard
Abstract : We investigate the effect of a reduction of anonymity on consumers' purchase decisions (whether to buy, and if so how much to pay) at an online music store with Pay‐What‐You‐Want (PWYW)‐like pricing and in an Internet experiment mimicking the real world situation. Revealing the customer's name, e‐mail, and payment to the artist (seller) led to insignificantly higher payments, although it drastically reduced the number of customers purchasing. Overall, the regime led to a revenue loss of 25%. In the online experiment, revenue drops by 35%. These results suggest that the positive effect of reduced anonymity, previously established for donation or public goods contexts, does not extend to a consumption environment. Instead, the substantial opt‐out of customers is likely to be motivated by concerns about privacy.